CHEMICAL ENVIRONMENT CHARACTERISTICS AND PHYSICAL ENVIRONMENT RISK FACTORS ASSOCIATED WITH MALARIA INCIDENCE IN SOWEK HEALTH CENTRE WORKING AREA, SUPIORI DISTRICT - Regina Iriani Caroline De Rosario Renyaan (Health Notions, 2023)
Malaria is still a health problem in Indonesia, where Papua is the highest contributor to malaria cases yearly. One of the areas contributing to malaria cases comes from Supiori Regency, with one of its working areas being the Sowek Health Centre. However, in recent years, it has been suppressed; in 2022, there was a 5-fold increase in cases compared to the previous year. The increase in malaria cases is inseparable from physical environmental factors and supported by a chemical environment that supports the breeding Anopheles mosquitoes. The method used was a cross-sectional study with a sample size of 70 people. The results showed that two variables were risk factors for malaria incidence, namely the condition of the walls of the house (p-value=0.009; OR=2.571 (95%CI=1.159-5.705)) and the condition of the ceiling (p-value=0.042; OR=1.673 (95%CI=1.034-3.358)) while for the chemical environment, the pH was in the range of 4.4-8.4 with a salinity level of 0.00/00 -150/00. Because of the potential of physical and chemical environmental factors, it is necessary for environmental control efforts to be carried out in order to optimize the prevention efforts that the Sowek Health Centre has carried out.